Acoustical, thermal, and morphological properties of zein reinforced oil palm empty fruit bunch fiber bio-composites - Elammaran, Jayamani; Sinin, Hamdan; Soon, Kok Heng; Md Rezaur, Rahman; Muhammad Khusairy, Bin Bakri (John Wiley and Sons Inc., 2016)
In this research, biodegradable composites were prepared with zein as a polymer matrix and oil palm empty fruit bunch (OPEFB) as fiber reinforcement. The fibers were treated with sodium hydroxide (NaOH). The effects of sodium hydroxide treatment on sound absorption, thermal stability, and fiber-polymer matrix interaction in composites were examined. The acoustical sound absorption coefficients of the composites were evaluated using two-microphone transfer function impedance tube method. The spectral, thermal, and morphological studies of the composites were analyzed and characterized using scanning electron microscope (SEM), thermogravimetric analysis (TGA), and Fourier transform infrared (FTIR) spectroscopy. It was found that in all the biodegradable composites, the sound absorption coefficients increased as the frequency increased. Increases in fiber loading caused sound absorption coefficients of the composites to increase. The sodium hydroxide treatment showed a better interface adhesion on fiber and zein matrix. It was also found that this treatment increased the sound absorption coefficients. This was supported by qualitative analysis on the SEM micrographs and FTIR spectrum.